Differentiated E-Module Based on Problem-Based Learning: Natural Science Subject - Harahap, Sari Maulina; Napitupulu, Efendi; Mursid, R. (RIRAI Publisher, 2024)
Finding out whether PBL-based differentiated e-modules are feasible, practical, and effective are the three main objectives of this project. This study uses the ADDIE paradigm (Analysis, Design, Develop, Implement, and Evaluate) in conjunction with the Research and Development (R&D) technique. Thirty seventh-grade earth and solar system students served as the study's subjects. In addition to phases of individual trials, small group trials, and field trials, this study included validation tests conducted by professionals in media, instructional design, and materials. The study's findings revealed: In the Very Feasible category, Material Experts scored 85.09, while Learning Design Experts scored 92.87. Extremely feasible Experts in Media Design scored 89.44 in the category of Very Feasible. Field trials scored 87.29 in the Very Feasible category, small group trials scored 87.30, and individual trials scored 87.27 in the Very Feasible category. At a significance threshold of α = 0.05, the computation yielded tcount = 4.256 and ttable = 1.67, indicating that tcount > ttable. These findings indicate that, at a significance level of 5%, there is a substantial difference between the learning outcomes of the students in the experimental and control classes, with H0 being rejected and Ha being accepted. According to the efficacy test's computation, According to the data, students who get instruction using PBL-based differentiated E-modules achieve better learning outcomes than those who receive printed books (81.25% > 73.33%). Therefore, it can be said that the Science on Earth and Solar System class VII PBL-based differentiated E-modules at SMP N 43 Medan are superior to using printed books.